The awareness of energy saving in UiTM Shah Alam hostels / Norhasdila Wirasak - Wirasak, Norhasdila (Faculty of Architecture, Planning and Surveying, 2013)
Energy saving is decreasing the amount of energy used. Using less energy has lots of benefits that it can save money and help the environment. Generating energy requires precious natural resources, for examples coal, oil or gas. Therefore, using less energy helps us to preserve these resources and make them last longer in the future. For example, allows a building to use less heating and cooling energy to achieve and maintain a comfortable temperature and installing fluorescent lights or natural skylights to reduce amount of energy required to achieved the same level of illumination compared with using traditional incandescent light bulbs. There are many ways to save energy that is turn off lights and appliances when are not used, use energysaving light bulbs, use rechargeable batteries instead of disposable batteries and choose products that come with lightweight packaging. The research carried out about the energy saving in UiTM Shah Alam hostels by following the aims and objectives of study which are included study on the types of energy saving, to investigate the awareness of students on energy saving and to carry out the suitable recommendation of the energy saving in UiTM Shah Alam hostels.